Pengaruh Air Rebusan Daun Sirih terhadap Keputihan Fisiologis pada Wanita Usia Subur di Desa Baturono Kecamatan Salam Kabupaten Magelang - Rifda Annisa Risviana; Fatimah Dewi Anggraeni; Nur Rahmawati S (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2024)
Vaginal discharge is one of the reproductive disorders often experienced by women in Indonesia caused by humid weather that affects the development of fungi. Continuous vaginal discharge affects the functioning of the female reproductive system. Overcoming vaginal discharge can be done with non-pharmacological therapy with red betel leaves. This study aims to determine the effect of betel leaf boiled water on physiological vaginal discharge in women of childbearing age in Baturono Village, Salam District, Magelang Regency. The research method used is quantitative research with a Quasy Experiment design using Two Groups Pre-Test and Post-Test with the control group. The population is 60 WUS, and the sample size is 30 respondents. The sampling technique uses Purposive Sampling. Statistical test using Paired T-Test. The result of this study was that the mean value 9pre-test0 given water treatment boiled red betel leaf was 14.80 and the mean value (post-test) was 5.27. So that the provision of red betel leaf boiled water has an effect on overcoming physiological vaginal discharge in Baturono Village based on the results of research p-value 0.000 < 0.5. So it can be concluded that there is an effect of giving red betel leaf boiled water on physiological vaginal discharge in women of childbearing age in Baturono Village, Salam District, Magelang Regency with a p-value of 0.000 < 0.5.